البرامج التلفزيونية العربية الموجهة للمرأة - صليحة مرزوق; دلال بن التواتي; د/عبد القادر علال (جامعة عمار ثليجي الاغواط, 2023)
ملخص الدراسة: ساهمت البرامج التلفزيونية من خلال محتوياتها في رسم تصورات تحاكي بها الواقع على ضوء القضايا التي تعالجها، وذلك حسب أهداف القائم بالاتصال والرسالة التي يريد تمريرها للمشاهد ونوع التأثير الذي يسعى إليه، فالمحتويات الإعلامية هي إمتداد للقوى الناعمة تؤثر في المتلقي على عدة أصعدة منها: السلوك، الفكر، الرأي، الإتجاه، القيم، فتغيره على المدى الطويل، وبالتالي هي سلاح ذو حدين يُبتغى نيله لإحداث التأثير من خلاله، خاصة برامج المرأة التي تعبر عنها وعن واقعها وأهدافها فتكون منبرا من خلاله تناضل وتدافع عن قضاياها وتحدث التأثير والتغيير، وكذلك البرامج النسائية العربية التي لعبت دورا هاما في تمثيل المرأة العربية وخلفيتها القيمية. ومن هنا تهدف هذه الدراسة للإجابة عن كيفية معالجة البرامج التلفزيونية العربية للمضامين الموجهة للمرأة كإشكاليه رئيسية تتفرع منها تساؤلات من حيث الشكل تعنى بالمدة المخصصة لعرض أركان برنامج "هي وبس"، واللغة المستخدمة فيه والقوالب الإعلامية وعناصر الإخراج الفني المعتمدة فيه، وتساؤلات من حيث المضمون تعنى بمعرفة طبيعة المواضيع التي تناولها برنامج "هي وبس" والأساليب الاقناعية المعتمدة فيه، والفاعلون والإتجاه السائد نحو القضايا التي يطرحها، والقيم والسمات المتضمنة فيه أيضا، وقد حاولنا الإجابة عنها إعتمادا على المنهج الوصفي التحليلي باستخدام أداة تحليل المضمون وتطبيقها على عينة الأسبوع الاصطناعي، فتوصلنا إلى النتائج التالية: برنامج "هي وبس" موجه للمرأة والرجل في المقام الأول ثم الأسرة والمجتمع، عالج البرنامج قضايا المرأة انطلاقا من الواقع الاجتماعي لها، وإحتوى على القيم الإيجابية أكثر من السلبية كالإحسان والحب، والسمات الرافضة أكثر من الداعمة كالقيم الدخيلة على المجتمع في الفكر والسلوك، تضمن البرنامج قيم الصراع وتبادل الأدوار بين الرجل والمرأة في معالجة القضايا العاطفية، كما اعتمد على التنويع في القوالب الفنية والمواضيع والمصادر، وعلى الاستمالات الاقناعية العاطفية أكثر من العقلية . Summary: Television programs have contributed, through their content, to shaping perceptions that simulate reality in light of the issues they address. This is in accordance with the objectives of the communication system and the message it aims to convey to the viewers, as well as the type of impact it seeks to achieve. Media content is an extension of soft power that influences the audience on several levels, including behaviour, thinking, opinion, direction, and values. It has the power to bring about long-term changes, making it a double-edged sword sought after for its potential to create an impact. Women's programs, in particular, express and represent women's realities, goals, struggles, and bring about influence and change. Similarly, Arab women's programs have played a significant role in representing Arab women and their cultural backgrounds. Hence, the aim of this study is to answer questions about how Arab television programs address content directed towards women as a key issue. These questions branch out into several aspects, such as the format of the program "Hya w Bas" in terms of the duration allocated to each segment, the language used, the media templates, and the technical production elements employed. Additionally, there are questions concerning the content itself, which involve understanding the nature of the topics covered in the program “Hya w Bas”, the persuasive techniques employed, the actors involved, the prevailing trends regarding the issues raised, and the values and attributes it encompasses. The study attempts to answer these questions using a descriptive analytical method, employing content analysis as a tool and applying it to a sample from an artificial week. The following results were obtained: the program "Hya w Bas" primarily targets women and men, followed by families and society. The program addresses women's issues based on their social reality and includes more positive values such as kindness and love than negative values. It contains more rejecting traits than supportive ones, particularly in terms of values foreign to society in terms of thought and behaviour. The program includes values of conflict and role exchange between men and women in addressing emotional issues. It also relies on diversity in artistic templates, topics, and sources, and emotional appeals more than rational ones.
دراسة تحليلية لبرنامج "هي وبس" على قناة CBC Sofra_